Challenges for Modeling Carbon Emissions of High-rise Public Residential Buildings in Hong Kong. (2015) - Zhao, Y.; Pan, W.; Ning, Y.
Abstract: The approach of low or zero carbon building (L/ZCB) has attracted increasing attention in both academic and professional fields as the carbon emissions attributable to buildings kept increasing in the past decades. However, there exist challenges with modeling the carbon emissions of high-rise buildings in high-density urban environments. The aim of this paper is to examine the challenges and develop strategies for modeling carbon emissions in high-rise public residential buildings within the context of Hong Kong. The paper first reviews the challenges facing the modeling of the carbon emissions of high-rise buildings both generally and in Hong Kong, and examines their relevant implications for building design decision making. The approaches to establishing reference building models, e.g. example, real and theoretical reference building, are investigated drawing on the regulatory and practical guidance for carbon emission modeling in Hong Kong. The paper then develops a simulation approach to analyzing the obstacles to building energy modeling for typical high-rise public residential buildings in Hong Kong. Considering the urban environmental factors that may contribute to biased results for energy simulation, this paper is focused on the technical issues during the conversion of data from BIM model to energy simulation software. Thermal zones and user behavior are also addressed since technical and subjective assumptions could lead the simulation to a wrong direction. Understanding of such challenges enables the energy simulation to perform smoothly and also informs carbon emission modeling for high-rise L/ZCBs in other urban settings.